Growth Performances and Proximate Composition of Mystus Cavasius (Hamilton, 1822) Cultured in Recirculating Aquaculture System Under Different Stocking Densities - Rahman, Md Mizanur; Mondal, Gouri; Mithu, MD Marufujjaman; Rabbane, Md Golam; Mustafa, Md Ghulam (Dhaka University Journal of Biological Sciences, 2020)
Experiment was conducted to evaluate the high density culture of Mystus cavasius and its effects on growth performances, survival rate and proximate composition of the fish in recirculating aquaculture system. Fishes were cultured at 571, 714, 857 and 1000 fries/m3 as the initial stocking density. No significant differences (p > 0.05) were found in specific growth rate, average daily gain, food conversation ratio, protein efficiency ratio, condition factor (k) and survival rate (%) of fish under the culture period of 120 days among the different stocking densities. The average survival rate was ≥ 99% among the treatments at the end of the culture period. The moisture contents were between 77.10 and 77.75%, ash content was 2.58 and 2.61%, crude protein was 15.86 and 16.07%, crude lipid was 5.45 and 5.68% with no significant differences (p > 0.05) among the treatments. There were no significant variations in DO, TAN, NO3-N, NO2-N and pH among the treatments during culture. This study showed that stocking density of at least 1000 fries/m3 was the best option as the total gain was highest compared to other lower densities under similar facilities. Dhaka Univ. J. Biol. Sci. 29(2): 137-145, 2020 (July)